2022
DOI: 10.3389/fcimb.2022.853212
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19 Patients With SARS-CoV-2 Positivity in Feces

Abstract: BackgroundSARS-CoV-2 is highly contagious and poses a great threat to epidemic control and prevention. The possibility of fecal-oral transmission has attracted increasing concern. However, viral shedding in feces has not been completely investigated.MethodsThis study retrospectively reviewed 97 confirmed coronavirus disease 2019 (COVID-19) patients hospitalized at the First Affiliated Hospital, School of Medicine, Zhejiang University, from January 19 to February 17, 2020. SARS-CoV-2 RNA in samples of sputum, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recent report revealed that 22 of the 133 patients admitted with COVID‐19 had an initial or follow‐up positive sputum or fecal sample after the conversion of their pharyngeal samples from positive to negative. 39 We are uncertain as to whether or not the 52 cases in the recovered group in our study had SARS‐CoV‐2 in additional body sites and its influences on immunological response. Systematic and simultaneous collection of specimens from multiple body sites during future evaluations may be necessary to clarify this potentially confounding factor.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A recent report revealed that 22 of the 133 patients admitted with COVID‐19 had an initial or follow‐up positive sputum or fecal sample after the conversion of their pharyngeal samples from positive to negative. 39 We are uncertain as to whether or not the 52 cases in the recovered group in our study had SARS‐CoV‐2 in additional body sites and its influences on immunological response. Systematic and simultaneous collection of specimens from multiple body sites during future evaluations may be necessary to clarify this potentially confounding factor.…”
Section: Discussionmentioning
confidence: 83%
“…We lack information on the current form of the pandemics, such as changes in treatment or the emergence of new varieties. A recent report revealed that 22 of the 133 patients admitted with COVID‐19 had an initial or follow‐up positive sputum or fecal sample after the conversion of their pharyngeal samples from positive to negative 39 . We are uncertain as to whether or not the 52 cases in the recovered group in our study had SARS‐CoV‐2 in additional body sites and its influences on immunological response.…”
Section: Discussionmentioning
confidence: 85%
“…However, some studies demonstrated that the clearance time of COVID-19 in the digestive tract was later than that in the respiratory tract [ 44 , 45 ]. Recently, Wu et al [ 15 ] found that fecal positivity for SARS-CoV-2 was independent from the manifestation of gastrointestinal symptoms or disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches pointed out how the fecal-oral transmission could be considered on par with airborne transmission [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as our comprehension of the virus and its pathophysiology has deepened, it has become evident that the impact of SARS-CoV-2 extends beyond the respiratory system, with the gastrointestinal (GI) tract being a notable site of involvement [4,5]. A significant subset of COVID-19 patients exhibits gastrointestinal symptoms, including diarrhea, nausea, and vomiting, and viral shedding in feces has been documented [5,6,7,8]. The propensity of SARS-CoV-2 to infect the GI tract is attributed to its utilization of the angiotensin-converting enzyme 2 (ACE2) receptor for cellular entry, a receptor abundantly expressed in various tissues, including the epithelial cells of the GI tract [9].…”
Section: Introductionmentioning
confidence: 99%